Genetic diversity and population structure of Culex modestus across Europe: does recent appearance in the United Kingdom reveal a tendency for geographical spread?. Issue 1 (11th October 2019) - Hernández‐Triana, L. M.; Brugman, V. A.; Pramual, P.; Barrero, E.; Nikolova, N. I.; Ruiz‐Arrondo, I.; Kaiser, A.; Krüger, A.; Lumley, S.; Osório, H. C.; Ignjatović‐Ćupina, A.; Petrić, D.; et al.
Abstract: In mainland Europe, the mosquito species Culex modestus Ficalbi (1890) is a bridge vector for West Nile virus (WNV) from its natural bird‐mosquito cycle to mammals. The present study assessed the genetic diversity of Cx. modestus, as well as related Culex species, using the mitochondrial COI DNA barcoding region and compared this with the population structure across Europe. A haplotype network was mapped to determine genealogical relationships among specimens. The intraspecific genetic diversity within individual Culex species was below 2%, whereas the interspecific genetic divergence varied from 2.99% to 13.74%. In total, 76 haplotypes were identified among 198 sequences. A median‐joining network determined from 198 COI sequences identified two major lineages that were separated by at least four mutation steps. A high level of intraspecific genetic diversity was not detected in Cx. modestus in samples submitted from different European populations, which indicates that morphologically identified specimens represent a single species and not a species complex. Therefore, it is deduced that different populations of Cx. modestus will show a similar potential to transmit WNV, lending support to concerns that the population present in southeast England represents a risk of transmission to humans. Abstract : The intraspecific genetic diversity within individual Culex species was below 2%, whereas the interspecific genetic divergence varied from 2.99% to 13.74%. In total, 76 haplotypes were identified among 198 sequences. A median‐joining network determined identified two major lineages in Culex modestus that were separated by four mutation steps. A trend of geographical associations of the lineages indicated that those species from the U.K. and Germany were in lineage II.